Impact of ablation ratio on 5-year postoperative posterior corneal stability after refractive surgery: SMILE and FS-LASIK - Li, Meiyan (Eye Vis (Lond), 2020)
BACKGROUND: To investigate the impact of the ablation ratio on 5-year postoperative posterior corneal stability in myopic eyes after small incision lenticule extraction (SMILE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK) surgery. METHODS: A prospective, nonrandomized, cohort study: 80 eyes of 43 patients underwent SMILE surgery and 63 eyes of 32 patients underwent FS-LASIK surgery at the EYE & ENT Hospital, Fudan University. Ablation ratio was defined as lenticule thickness (SMILE cases) or ablation depth (FS-LASIK cases) divided by central corneal thickness (CCT). Posterior corneal elevation changes were recorded as posterior central elevation (PCE), posterior corneal surface at thinnest point (PTE) and posterior corneal mean elevation (PME). Patients were followed up at 6-month and 5-year interval to investigate the impact of the ablation ratio on posterior corneal elevation after SMILE and FS-LASIK surgery. RESULTS: PCE dropped at the 6-month follow-up for both SMILE (decreased by −1.11 ± 2.93 μm, P < 0.05) and FS-LASIK groups (decreased by −0.46 ± 3.72 μm, P < 0.05). PTE also dropped in SMILE (reduced by −2.04 ± 3.02 μm, P < 0.05) and FS-LASIK group (reduced by −1.28 ± 4.21 μm, P < 0.05) at the 6-month follow-up. Stable PCE (elevation change: SMILE −0.28 ± 4.03 μm; FS-LASIK 0.79 ± 4.13 μm, P > 0.05) and PTE (elevation change: SMILE −0.08 ± 4.28 μm; FS-LASIK 1.42 ± 3.85 μm, P > 0.05) for both groups were recorded at the 5-year follow-up compared to the 6-month visit. Ablation ratio was strongly correlated with 5-year postoperative PCE (β = 2.68 ± 1.05, P < 0.01) and PTE (β = 2.35 ± 1.17, P < 0.05). Cut-off value for 5-year postoperative raised PCE and PTE was 27.3 and 27.1%, respectively. CONCLUSIONS: Ablation ratio was strongly correlated with postoperative posterior corneal elevation in a 5-year follow-up in both SMILE and FS-LASIK groups. PCE and PTE underwent slight backward displacement 6-month postoperatively and remain stable at the 5-year follow-up. Threshold of the ablation ratio for resisting forward displacement of posterior corneal surface was 27.3 and 27.1% for SMILE and FS-LASIK groups, respectively.